Sustainability in multi-religious societies: an Islamic perspective - Grine, Fadila; Bensaid, Benaouda; Roslan, Noor (Taylor & Francis Group, 2013)
The question of sustainability in multi-religious societies underscores many interrelated theological, moral, legal and socio-cultural issues affecting the very process of social co-existence, cohesion and development. This paper discusses Islam’s stand on sustainability in multi-religious contexts while highlighting its perspective on the religious, spiritual and moral pre-requisites of sustainability. This study also sheds light on a number of key concepts and core values in Islam related to shaping sustainable development in multi-religious societies. This inquiry on the perspective of Islam towards sustainability provides an understanding of not only the religious implication of sustainability but equally highlights a number of critical factors required for development in multi-religious societies.